2007
DOI: 10.1089/lap.2006.0102
|View full text |Cite
|
Sign up to set email alerts
|

Midgut Volvulus Following Laparoscopic Gastric Banding—A Rare and Dangerous Situation

Abstract: Intestinal malrotation is usually encountered in infants. Its main complication is midgut volvulus, a situation that presents itself with bilious vomiting. This symptom allows for early surgical treatment. A delay in diagnosis and treatment may lead to catastrophic sequelae, such as extensive bowel necrosis and death. This situation is rare but well known in adults. Laparoscopic gastric banding is a popular option for treating morbid obesity. One of the consequences of this procedure may be impaired vomiting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Features of intestinal obstruction in patients who have had previous laparotomy always raise the suspicion of adhesions as the aetiological factor. The other possible causes to consider are either postoperative midgut volvulus or internal herniation and few of the latter have been reported following laparoscopic appendicectomy, cholecystectomy and gastric banding operations [12][13][14] . The reason(s) for this rare phenomenon following laparoscopic operations is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Features of intestinal obstruction in patients who have had previous laparotomy always raise the suspicion of adhesions as the aetiological factor. The other possible causes to consider are either postoperative midgut volvulus or internal herniation and few of the latter have been reported following laparoscopic appendicectomy, cholecystectomy and gastric banding operations [12][13][14] . The reason(s) for this rare phenomenon following laparoscopic operations is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Erenbourg was described a ligament called 'gastro-pancreatic', and they suggested that the presence of this anatomic element can suggest new interpretations of the embryological development of the pancreas [3]. Several gastric volvulus cases have been reported after laparoscopic gastric banding, usually occurring after placement of the band [4][5][6]. They recommended not to dissect the posterior wall of the stomach during band replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Volvulus blocks blood flow and leads to ischemia followed by necrosis. It can affect older children and adults as a late manifestation of malrotation (2,3) or from complication of a previous surgery, as an adherence or stoma may act as an axis around which the twisting occurs (4) . Volvulus occurring in the absence of malrotation and previous surgeries in patients submitted to laparoscopic surgery is rare, and few cases have been recently reported.…”
Section: Discussionmentioning
confidence: 99%